Dynamics of biological parameters of spawners of pacific salmons returned to the rivers of the Avachinsky Bay (south-eastern Kamchatka) in 1989-2014 - Oleg M. Zaporozhets; Galina V. Zaporozhets; Zhanna Kh. Zorbidi (Известия ТИНРО, 2016)
Dynamics of biological parameters for adults of chum, sockeye, pink, coho, and chinook salmons in the rivers of the Avachinsky Bay is analyzed. There is shown for three populations of sockeye salmon that general age of the returned adults correlates positively with duration of their fresh-water life but negatively with timing of their approach for spawning. Tendency to decreasing of weight is revealed for chinook females, but weight of their males is stable. Dynamics of weight and timing of spawning run is significantly different for pink and chum salmons of the rivers Avacha and Nalycheva. Weight of coho females has negative trend, in spite of stable fecundity and age of return.